Avaliação da qualidade de vida dos pacientes portadores de estomias intestinais - Duarte, Andréia Majella da Silva (2009)
An intestinal stoma produces numerous changes in patients' lives, a fact that requires adaptation and can change their quality of life. Therefore, this study aimed at evaluating the quality of life of patients with intestinal stomas registered in the Ostomized Patient Program of Stoma of an outpatient service in a municipality in southern Minas Gerais, Brazil. This is an epidemiological, descriptive, cross-sectional quantitative study that included 13 ostomized patients who were interviewed at home in July and August 2007. Two instruments were used to collect data: (1) characterization of participants and (2) the WHOQOL-Bref, for the "quality of life". For data collection, the interviewees signed an informed consent form, and the protocol was approved by the UNIFENAS Committee of Ethics in Research. The software SPSS version 10 was used for data analysis and the Chi-square and the Cronbach alpha tests were used for the crossing of variables. The results showed that most of the patients were 61 years or older, female, from urban areas, catholic, had elementary school; widow / separated / divorced, had 1 to 3 children and family income of 4 to 6 times the minimum wage. With respect to the physiological need for sleep, 61.5% of the population studied had insomnia, a situation that was aggravated after ostomy. Most of them reported 1 to 2 intestinal evacuations per day, with a pasty consistency. Their greatest difficulty was to adapt themselves to the stoma. When crossing gender and marital status with the difficulty of adapting to the bag and self-care, there was statistical significance. Most respondents did not return to sports, work, and sexual and social activities after ostomy, and showed increased feelings of loneliness, contempt, tearfulness and dependence. Their family was the main help. The most evident complications were bleeding and peristomal dermatitis. With regard to the rights of the ostomized, 84.6% reported having been informed by the physician and / or outpatient clinic and the main way of acquiring the collection equipment is through the SUS, free of charge. The measurements of the quality of life of this population were: mean score of overall QOL, 3.61; physical domain, 3.40; psychological domain, 3.43; social relationships domain, 3.46;and the environment domain, 3, 49. The higher average scores rated the quality of life as being above the "neither bad nor good." The WHOQOL-bref was effective to evaluate the QOL of patients with intestinal stomas, with internal consistency above 0.72. Finally, it is important that the ostomized patients be informed about their disease, and receive emotional support and rehabilitation care in order to be able to lead an active, productive and self-sufficient life.